ENHANCING STUDENT LEARNING MOTIVATION THROUGH THE SYNERGY OF THE TALKING STICK MODEL AND CHOOSE NUMBER MEDIA ON THE NERVOUS SYSTEM TOPIC - Dewi, Cut Ratna; Azhani, Nazuhra; Fajriana, Nurul (Prodi Tadris Biologi Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2025)
Learning motivation is a crucial factor in determining the success of classroom learning. However, based on initial observations, a lower level of student learning motivation was found, specifically regarding the nervous system material. This study aims to analyze the improvement of learning motivation in eleventh-grade high school students through the application of the Talking Stick learning model combined with Choose Number media on the nervous system topic. The research method used was quantitative with a Quasi experimental design approach, employing a non equivalent contol group design. Data collection techniques utilized observation and questionnaires with research intruments in the form of observation sheets and motivation questionnaires. Data analysis was conducted using percentage formulas. The results of this study indicate a significant increase in the average percentage of student learning motivation in the experimental class, reaching 82.9%, which falls into the very high category. It can therefore be concluded that the application of the Talking Stick learning model integrated with Choose Number media is effective in enhancing student learning motivation regarding the nervous system material within the experimental class.otivation questionnaires. Data analysis was conducted using percentage formulas.